Sampādaka-sāhityakāra Padumalāla-Punnālāla Bakhśī - Jhā, Añjanī Kumāra, 1969- (Gājiyābāda : Mañju Buksa Senṭara, 2017)
Study of the works of Padumalāla Punnālāla Bakhśī, Hindi author.
In Hindi.
Keywords: Bakhśī, Padumalāla Punnālāla, -- 1894-1971 -- Criticism and interpretation; Bakhśī, Padumalāla Punnālāla, -- 1894-1971.; Criticism, interpretation, etc